2019
DOI: 10.2217/epi-2019-0009
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of differences of N 6 -methyladenosine RNA methylomes between high-fat-fed and normal mouse livers

Abstract: Aim: To assess the m6A methylome in mouse fatty liver induced by a high-fat diet (HFD). Materials & methods: MeRIP-seq was performed to identify differences in the m6A methylomes between the normal liver and fatty liver induced by an HFD. Results: As compared with the control group, the upmethylated coding genes upon feeding an HFD were primarily enriched in processes associated with lipid metabolism, while genes with downmethylation were enriched in processes associated with metabolism and translation. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
39
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 56 publications
11
39
2
Order By: Relevance
“…Next, we further analyzed the distribution of ac 4 C peaks per gene between the two groups. Intriguingly, in the SLE and HC groups, the majority of ac 4 C-modified transcripts were observed to have one or two ac 4 C peak(s) per gene (77.06 and 86.53%, respectively), while a very small number of transcripts contained three or more ac 4 C peaks ( Figure 2C), which is similar to the trend of m 6 A characteristics previously reported in abnormal mouse livers (Luo et al, 2019). Furthermore, the proportion of ac 4 C-modified transcripts harboring only one ac 4 C peak was lower in CD4 + T cells of SLE groups (63.87% vs. 53.03%) than in HCs; whereas, the percentage of transcripts harboring two or more ac 4 C peaks was higher.…”
Section: Transcriptome-wide Global Ac 4 C Modification In Sle Patientsupporting
confidence: 87%
“…Next, we further analyzed the distribution of ac 4 C peaks per gene between the two groups. Intriguingly, in the SLE and HC groups, the majority of ac 4 C-modified transcripts were observed to have one or two ac 4 C peak(s) per gene (77.06 and 86.53%, respectively), while a very small number of transcripts contained three or more ac 4 C peaks ( Figure 2C), which is similar to the trend of m 6 A characteristics previously reported in abnormal mouse livers (Luo et al, 2019). Furthermore, the proportion of ac 4 C-modified transcripts harboring only one ac 4 C peak was lower in CD4 + T cells of SLE groups (63.87% vs. 53.03%) than in HCs; whereas, the percentage of transcripts harboring two or more ac 4 C peaks was higher.…”
Section: Transcriptome-wide Global Ac 4 C Modification In Sle Patientsupporting
confidence: 87%
“…Methylated RNA immunoprecipitation sequencing (MeRIP-seq) was performed based on a previously reported procedure [32]. Total RNA was lysed into 100 base pair fragments using a GenSeqTM m5C RNA IP Kit (GenSeq Inc, China), and m5C immunoprecipitation was performed followed by RNA-seq library generation using a NEBNext Âź Ultra II Directional RNA Library Prep Kit (New England Biolabs, Inc, USA).…”
Section: Library Construction and Sequencingmentioning
confidence: 99%
“…The pathological character of NAFLD is caused by metabolic dysregulation of de novo lipogenesis, fatty acid uptake, fatty acid oxidation, and triglycerides export [97,98]. Previous studies have found that m 6 A alteration is highly related to the development of NAFLD [34,99,100]. The level of FTO is elevated in hepatic tissue at NAFLD patients with hyperglycemic and hyper-insulinemic [34], which can down-regulate mitochondrial content and upregulate triglyceride (TG) deposition, while FTO (R316A) mutant lacking demethylation activity and could not regulate mitochondria and TG content.…”
Section: A Methylation and Nafldmentioning
confidence: 99%